COMMUNITY EMPOWERMENT AGAINST SOCIAL INEQUALITIES IN THE CIPONDOH DISTRICT: English - Wahyunengsih, Wahyunengsih; Nadzifah, Salsa Layyinun (LPPM Univ. Ibn Khaldun Bogor, 2023)
Inequality means an imbalance in a population and is something that can change an environment to become out of sync due to the unevenness of a different social identity in the same place. And empowerment is the authority of a human destiny that is carried out by other humans in order to complement and balance a destiny in society. Empowerment is usually done in an environment to facilitate environmental development and reduce social inequality.